Achieving enhanced material finishing using cold plasma treatments. (28th May 2015) - Dowling, D. P.; Stallard, C. P.
<x content-type="archive" xml:space="preserve">Abstract</x> Plasma processing treatments are used widely in materials finishing. The plasmas used for these applications can be either 'hot' or 'cold'. Examples of the former include those used in thermal spray and arc discharge machining. Cold plasmas, which are the focus of this review, are used for relatively low temperature surface cleaning and polymer activation. Cold plasmas can also be used for the deposition of coatings including plasma polymerised thin films. These nanometre thick polymer layers exhibit a tailored chemical functionality and can be used, for example, to control surface wetting properties ranging from superhydrophilic to superhydrophobic (SH). These cold plasmas can be operated under both low pressure and atmospheric conditions. Commercial materials finishing applications of 'cold' plasma treatments are highlighted.